Quem Instrui os Instrutores? - Chinen, Nobuyoshi (9 Arte (São Paulo), 2012)
SANTOS NETO, Elydio dos; SILVA, Marta Regina Paulo da (organizadores). Histórias em quadrinhos & educação. São Bernardo do Campo: Universidade Metodista de São Paulo, 2011.